Design and Implementation of a Manually Portable Device to Spectroscopically Assess Fruit Quality - (:unkn) unknown (IEEE, 2014)
As they are directly related to people's health and social progress, food safety and quality are important issues in food industry. A rapid nondestructive sensing technique will be very useful to monitor and manage different working steps in horticultural production, at harvest as well as in pre-harvest and postharvest processing. Due to fast response, the influence of different external factors like geographical site, weather and soil conditions, nutrition status, and alike can be assessed early-on during plant development and the producer may take appropriate measures at an earlier date than conventional. External properties such as shape, color, size, firmness, and alike are indicators of internal properties, such as soluble solids content, acidity, vitamin content, sugar content, water content, and alike. Evaluating data obtained from preliminary laboratory studies by using a spectrophotometer, a prototype manually portable device which measures in 400 to 1100 nm wavelength range was developed. Thanks to LED light sources, thermal damage to the tested fruit tissue is prevented. Users can easily control the device and are able to monitor measurements with appropriate hardware and firmware interface. In addition, with measurement transmitted to a computer using Bluetooth technology, processing and assessment of data is easily managed.
Keywords: NEAR-INFRARED SPECTROSCOPY; SOLIDS